An experimental field study of inbreeding depression in an outcrossing invasive plant - Balogh, Christopher M.; Barrett, Spencer C. H. (Frontiers in Plant Science, 2024)
Inbreeding depression is likely to play an important role during biological invasion. But relatively few studies have investigated the fitness of selfed and outcrossed offspring in selfincompatible invasive plants in natural environments in their introduced range. Moreover, the majority of studies on inbreeding depression have investigated self-compatible species with mixed mating, and less is known about the intensity of inbreeding depression in outcrossing self-incompatible species. Here, we address these questions experimentally by comparing selfed and outcrossed progeny of purple loosestrife (Lythrum salicaria) over four growing seasons, including three under field conditions in a freshwater marsh in southern Ontario, Canada, a region where L. salicaria is highly invasive. The tristylous mating system of L. salicaria involves disassortative mating among floral morphs enforced by trimorphic incompatibility. However, owing to partial incompatibility, self-fertilized seed can be obtained by manual self-pollination thus facilitating comparisons of selfed and outcrossed progeny.We compared progeny with and without intraspecific competition from selfed or outcrossed neighbours and examined the influence of breeding treatment and competition on fitness correlates by measuring a range of life-history traits including: proportion of seeds germinating, days to germination, survival, proportion of plants flowering, time to flowering, vegetative mass, and inflorescence number and mass. We analysed data for each trait using functions from time series estimates of growth and two multiplicative estimates of fitness. We detected varying intensities of inbreeding depression for several traits in three of the four years of the experiment, including inflorescence mass and reproductive output. Cumulative inbreeding depression over four years averaged δ = 0.48 and 0.68, depending on the method used to estimate multiplicative fitness. The competition treatments did not significantly affect plant performance and the magnitude of inbreeding depression. Given the primarily outcrossing mating system of L. salicaria populations, the detection of inbreeding depression for several key life-history traits was as predicted by theory. Our results suggests that biparental inbreeding and low selfing in colonizing populations may have significant effects on demographic parameters such as population growth.